2002
DOI: 10.1046/j.1440-1746.2002.02880.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Helicobacter pylori‐induced interleukin‐8 production in gastric cancer cell lines by an anti‐ulcer drug, geranylgeranylacetone

Abstract: Helicobacter pylori-infected gastric mucosal cells produce IL-8, which can promote neutrophil activation, thus contributing to mucosal tissue injury associated with H. pylori infection. Agents like GGA, which can suppress IL-8 production may have a protective role in the treatment of mucosal tissue damage seen in H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…It is thought that treatment with GGA suppresses the increase in neutrophil accumulation in the colons of mice with TNBS-induced colitis. Recently, it has been reported that GGA regulates the expression of interleukin-8 in the gastric mucosa (34,35). Although the mechanism by which GGA suppressed neutrophil accumulation in colon tissue from mice with TNBS-induced colitis was not clarified in the present study, previous studies and the present study suggest that GGA inhibits neutrophil accumulation via mediating the expressions of chemokines in the colon.…”
Section: Discussioncontrasting
confidence: 54%
“…It is thought that treatment with GGA suppresses the increase in neutrophil accumulation in the colons of mice with TNBS-induced colitis. Recently, it has been reported that GGA regulates the expression of interleukin-8 in the gastric mucosa (34,35). Although the mechanism by which GGA suppressed neutrophil accumulation in colon tissue from mice with TNBS-induced colitis was not clarified in the present study, previous studies and the present study suggest that GGA inhibits neutrophil accumulation via mediating the expressions of chemokines in the colon.…”
Section: Discussioncontrasting
confidence: 54%
“…We therefore speculated that the decrease of H. pylori colonization density produced by teprenone in the corpus might be accounted for by other mechanisms. Recently, Yoshimura et al have also reported that teprenone at 0.1 mmol/l inhibits IL-8 mRNA expression in H. pylori-infected gastric mucosal cells (KATOIII cells) up to approximately 50% [29]. In fact, it has been shown that IL-8 levels correlate with H. pylori density and intensity of neutrophil infiltration in the gastric mucosa [28].…”
Section: Discussionmentioning
confidence: 97%
“…The inhibition rate was up to approximately 50% for 0.05 mmol/l teprenone. Recently, Yoshimura et al have also reported that teprenone at 0.1 mmol/l inhibits IL-8 mRNA expression in H. pylori-infected gastric mucosal cells (KATOIII cells) up to approximately 50% [29]. Based on our in vitro findings for teprenone, it is likely that orally administered teprenone actually inhibits IL-8 production in the gastric mucosa, because it has been confirmed that therapeutic oral doses of teprenone will reach 0.01-0.1 mmol / l in the mucosa [30].…”
Section: Discussionmentioning
confidence: 98%
“…Highly expressed levels of IL-8 mRNA and protein were found in gastric cancer cells [8], [9]. It has recently been suggested that IL-8 is closely related to the tumorigenesis, angiogenesis, adhesion, invasion or metastasis of cancer [10][14].…”
Section: Introductionmentioning
confidence: 99%